(untitled) (Zoological Records and Reviews, 2024)
Animals occupying thermally extreme environments–polar regions, hyper-arid deserts, hydrothermal vents, and high-altitude plateaux–have evolved a diverse suite of morphological, physiological, and behavioural adaptations that enable survival and reproduction under conditions lethal to most species. This comparative study quantifies key adaptive traits in 24 vertebrate and invertebrate taxa representing four extreme climate zones: Arctic/Antarctic (n = 6 taxa), hot desert (n = 6), high altitude (n = 6), and deep-sea hydrothermal vent (n = 6). Trait data were compiled from field measurements and laboratory experiments conducted across Denmark, France, and partner institutions between 2019 and 2023 (n = 847 individual measurements). Thermal tolerance breadth (CTmax - CTmin) ranged from 4.2degC in the stenothermal Antarctic icefish Chionodraco hamatus to 52.8degC in the Saharan silver ant Cataglyphis bombycina, the widest recorded tolerance in any animal. Basal metabolic rate (BMR) in polar endotherms was 38-67% higher than predicted by Kleiber’s allometric equation, while desert ectotherms exhibited BMR suppression of 31-54% during aestivation. Haemoglobin oxygen affinity (P50) in high-altitude taxa was 18-34% lower than sea-level congeners, conferring enhanced oxygen loading at reduced partial pressures. Molecular chaperone (Hsp70) expression levels under heat stress were 4.2-fold higher in desert-adapted taxa than in temperate controls. These findings are synthesised into a cross-taxa adaptation framework linking environmental extremity index to trait divergence magnitude, providing a quantitative baseline for predicting vulnerability of extreme-climate specialists to ongoing climate change.